Tween-80 Medium-Spectrophotometric Determination of Trace Ge(IV) with 1-(4-Antipyrine)-3-(2,4,6-tribromo phenyl)triazene as Colour Reagent - Zhang, Xue-Hong; Chen, Wen-Bin (Asian Journal of Chemistry, 2013)
A new triazene reagent 1-(4-antipyrine)-3-(2,4,6-tribromo phenyl)triazene was studied along with the colour reaction of 1-(4-antipyrine)-3-(2,4,6-tribromo phenyl)triazene with Ge(IV) in the presence of Tween-80. A highly sensitive new spectrophotometric method for the determination of trace Ge(IV) has proposed. The results showed that in Na2B4O7-NaOH medium at pH 9.50, the new colour reagent reacts with Ge(IV) to form a red complex (1:2). The maxium absorption wavelength and apparent molar absorptivity are 498 nm and 2.9 × 105 L mol-1 cm-1, respectively. Beer’s law is obeyed in the range of 0.01 to 2.8 μg/10 mL for Ge(IV). The colour reaction system could tolerate many interfering ions due to the existence of ammonia, the detection limit is 0.006 μg/10 mL. The RSD and recovery were 2.14-2.42 % (n = 6) and 103.2-104.1 %. The method has been applied to the determination of trace amount of Ge(IV) in tea.